Three-dimensional analysis using a dental model scanner: Morphological changes of occlusal appliances used for sleep bruxism under dry and wet conditions. - Aya Ozawa; Yoshitaka Suzuki; Kazuo Okura; Toshinori Okawa; Susumu Abe; Kohei Kamoi; Emi Uyama; Kenichi Hamada; Yoshizo Matuka (PLoS ONE)
Objective This study used a dental model scanner and best-fit alignment to analyze the deformation patterns of stabilized occlusal appliances (OcAs) used to treat sleep bruxism when stored in wet or dry conditions. Methods Eight OcAs were prepared using polymethyl methacrylate, stored in water at room temperature for 4 weeks (wet storage), and then in air for 4 weeks (dry storage). After being stored in water for one month for hydration, they were 3D-scanned and digitized on days 0, 28, and 56. 3D-deformation patterns were obtained by comparing the storage-D group data using a best-fit alignment program that aligns the nearest points of the corresponding images in a virtual space and calculates the difference between the two images. The maximum deviation and deformed area in the ± direction, and the volume of the wet (W) and the dry (D) condition groups were compared using Wilcoxon's signed rank test. Results OcA showed no obvious deformities in the W group at 4 weeks. However, in the D Group, a typical deformation pattern was detected at 4 weeks, with the posterior margin of the molars shrinking anteriorly, the palatal side of the molars lifted, and the buccal side retracted inward. The Ⅾ group was significantly larger than the W groups in terms of maximum deviation in the ± direction, deformed area, and volume. Conclusions After 4 weeks of storage under dry conditions, OcA showed a typical deformation pattern of shrinkage toward the center, with in-center lifting toward the palatal side. Significantly greater surface deviations, deformation areas, and deformation volumes were observed under dry conditions than in wet conditions.